Legal Assurance of the Land Registration Process in the Pandemic Time of Covid-19 - Rahmat Ramadhani; Rachmad Abduh (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Circular work from home for land office employees needs to be examined whether there is a change in the mechanism in legal certainty of land registration during the Covid-19 pandemic, whether the process of measuring land and signing witnesses whose land borders comply with health protocols outside the land office, especially in the field. The issues that will be studied are the implementation of the land registration process during the Covid-19 pandemic and legal certainty in the implementation of the land registration process during the Covid-19 pandemic. The results show that the land registration process during the Covid-19 pandemic is still the same as before this outbreak, and regarding legal certainty, there are no specific rules regarding the obligation to comply with health protocols when undergoing the land registration process, especially in the field.